Traditional Omani Crafts Approaches To Identity - Almamari, Badar Mohammed; Fakhriya Al-Yahayai,; Alamri, Mohammed (Technium Social Sciences Journal, 2020)
The purpose of this study is to identify how landscapes, places, and geographical forms of land influenced craft making identity by addressing Omani crafts enterprises in urban and rural areas. This has been done by interviewing local craftspeople and analysing their responses as a qualitative data collection method using open-ended questions to seek reliability and credibility in the study. The interviews in this research were mostly conducted with participants belonging to ten enterprises under the management of the Public Authority for Crafts Industries (PACI), Department of Art Education and the Handcrafts Centre. Consequently, this study highlights the importance of studying the influence of landscapes, places, and geographical forms in shaping local people's crafts identity by investigating their craft industries in rural and urban areas.